Fikih Dakwah - Zulkarnaini Zulkarnaini (Universitas Islam Negeri Imam Bonjol Padang, 2010)
Although the title of this article have the word fiqh, but its position is not the same as others jurisprudence, like jurisprudence, prayer, zakat fiqh, fiqh hajj and others. In the systematic chapters of fiqh in general can not find a special section on propaganda. Grouping fiqh chapters which are found include: fiqh of worship, “fikih mu'amalah”, “fikih munakahat”, “fikih jinayah”, “fikih siyasah“, “fikih mawarits” and “fiqh murafa'ah”. Even if the books of fiqh discusses the mission, only a special glimpse of “al-amr bi al-ma'ruf wa al-nahy 'an al-munkar” in the chapter of “al-nizam al-Islam fi hukm” namely in the chapter Imamate, the discussion about the obligation of Muslims to support the authorities and the discussion of al-Hisbah Region. In the article the author tries to discuss about the issue: First, what is meant by proselytizing jurisprudence. Second, the mission in perspective Jurisprudence Jurisprudence and third missionary interpreters.